3D evaluation of the morphological and volumetric changes of the tongue and oral cavity before and after orthognathic surgery for mandibular prognathism: a preliminary study - Airy Teramoto; Shoichi Suzuki; Norihisa Higashihori; Naoto Ohbayashi; Toru Kurabayashi; Keiji Moriyama (SpringerOpen, 2020)
Abstract Background The volumetric ratio of the tongue to the oral cavity has been recognized to be one of the important factors for the maintenance of stable occlusion. Oral cavity capacity is changed after orthognathic surgery in patients with mandibular prognathism; however, the volumetric changes of the oral cavity including the tongue before and after surgery have not been analyzed. The purpose of this study was to evaluate the morphological and volumetric changes of the tongue and oral cavity following orthognathic surgery using a newly developed vinyl polysiloxane impression method. Materials and methods The study was performed in fifteen subjects who underwent surgical orthognathic treatment. Impressions of the tongue together with the oral cavity were obtained before orthognathic surgery and 1, 3, and 6 months after orthognathic surgery. These impression patterns were scanned using cone-beam computed tomography (CT), and three-dimensional (3D) images of the oral cavity including the tongue, and the upper and lower dental arches were reconstructed. The morphological and volumetric changes in the oral cavity capacity and the tongue volume were examined. Results The volume of the tongue with the volume of the oral cavity decreased after orthognathic surgery. There was a correlation between the decrease in the oral cavity capacity and tongue volume. The volumetric ratio of the tongue to the oral cavity seems to be maintained before and after orthognathic surgery. Conclusion VPS method, free from radiation exposure, may be useful for investigating the morphological and volumetric changes of the tongue and oral cavity, which may possibly influence the stability of the dental arch and occlusion during surgical orthodontic treatment.